Credit Risk Management and Sub-Standard Loans of Commercial Banks in Nigeria: A Panel Data Analysis - Nwosi, Anele Andrew; Nwakaego , Akani Elfreda (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2021)
This study examined the effect of credit risk management on sub-standard loan portfolio of quoted commercial banks in Nigeria. Cross sectional data was sourced from financial statement of commercial banks and Central Bank of Nigeria Statistical bulletin from 2009-2018. Sub-standard portfolio was used as dependent variable while bank risk diversification, Basel risk compliance, risk transfer were used as independent variables. Panel data methodology was employed while the fixed effects model was used as estimation technique at 5% level of significance. Fixed effects, random effects and pooled estimates were tested while the Hausman test was used to determine the best fit. Panel unit roots and panel cointegration analysis were conducted on the study. The empirical results proved that 41.7 per cent variations in the sub-sub-standard loans’ portfolio was explained by credit risk management. From the random effect results, bank risk transfer and Basel compliance have positive relationship with sub-standard loan portfolio while risk bank risk diversification have negative relationship with sub-stand ad loan portfolio of the commercial banks. We recommend that management of the commercial banks should be pro-active and devise effective measures of managing credit risk to reduce the incidence of sub-standard loans. The monetary authority should monitor the Basel compliance rate and policies of the commercial banks to credit risk management